(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a guidebook-based intervention on improving knowledge, attitudes, skills, and access to and utilization of services for children with autism spectrum disorder (ASD) among parents in Hanoi, Vietnam, 2024–2025. Methods: Pre–post intervention study without a control group was conducted among 191 parents or primary caregivers of children under 15 years of age diagnosed with ASD at five specialized centers in Hanoi. Participants received a structured guidebook on ASD care and service navigation and were assessed at baseline and after 3 and 6 months using standardized questionnaires on knowledge, attitudes, practices, and service use. Data were analyzed using descriptive statistics and paired pre–post comparison tests. Results: Following the intervention, the proportion of parents with adequate knowledge increased from 24.6% at baseline to 85.6% at 3 months and 96.5% at 6 months (p<0.001), with many knowledge items improving by 30–60% at 6 months. Positive attitudes toward early intervention and inclusive education increased markedly, particularly in domains with lower baseline agreement. Regular use of the guidebook increased from 66% to 74.5% (p<0.05). Mean confidence scores in ASD-related knowledge and caregiving skills improved significantly across all items. Overall satisfaction with the guidebook increased from 63.9% at 3 months to nearly 85% at 6 months. Conclusions: The guidebook-based intervention is a feasible, low-cost, and effective approach to improving parental knowledge, attitudes, skills, and access to ASD-related services. This tool could be scaled up and integrated into community-based ASD care and family support systems.